Optimal Crop Planting Scheme Based on Mixed Integer Programming - Ye, Haitao; Li, Xinhan; Shen, Dongjie (Transactions on Environment, Energy and Earth Sciences, 2024)
In order to achieve sustainable development of rural economy, make full use of limited cultivated land resources, improve production efficiency, reduce planting risks, and consider the actual rural situation and crop yield per mu affected by climate, market and other factors. It is necessary to comprehensively consider the expected sales volume, yield per mu, uncertainty of planting cost and selling price of various crops and potential risks, and give the optimal planting plan of crops. First, the maximum expected benefit is taken as the objective function, the planting area of crops planted in each plot in each season of the year is taken as the decision variable, and the influence of uncertain factors such as climate and market conditions is comprehensively considered. The parameter change model of each situation in which the uncertain factors are represented is established, and the objective function, constraints and uncertainties are comprehensively considered. Using Monte Carlo simulation optimization algorithm, the Monte Carlo optimal benefit model is established. Through programming solution, we obtained that the planting plots of similar crops were concentrated, and most of them only planted one crop in one plot, or at most two crops in one plot. In this paper, the Monte Carlo simulation algorithm is innovatively adopted to fully consider the uncertainties of crop sales volume, price, per mu yield and planting cost, making the decision more scientific and reasonable.